Computer-aided engineering of stabilized fibroblast growth factor 21 - de La Bourdonnaye, Gabin; Ghazalova, Tereza; Fojtik, Petr; Kutalkova, Katerina; Bednar, David; Damborsky, Jiri; Rotrekl, Vladimir; Stepankova, Veronika; Chaloupkova, Radka (Computational and structural biotechnology journal, 2024)
FGF21 is an endocrine signaling protein belonging to the family of fibroblast growth factors (FGFs). It has emerged as a molecule of interest for treating various metabolic diseases due to its role in regulating glucogenesis and ketogenesis in the liver. However, FGF21 is prone to heat, proteolytic, and acid-mediated degradation, and its low molecular weight makes it susceptible to kidney clearance, significantly reducing its therapeutic potential. Protein engineering studies addressing these challenges have generally shown that increasing the thermostability of FGF21 led to improved pharmacokinetics. Here, we describe the computer-aided design and experimental characterization of FGF21 variants with enhanced melting temperature up to 15 °C, uncompromised efficacy at activation of MAPK/ERK signaling in Hep G2 cell culture, and ability to stimulate proliferation of Hep G2 and NIH 3T3 fibroblasts cells comparable with FGF21-WT. We propose that stabilizing the FGF21 molecule by rational design should be combined with other reported stabilization strategies to maximize the pharmaceutical potential of FGF21.
Keywords: Fibroblast growth factor 21; Protein engineering; Protein stabilization